The state of Soviet agriculture in the post-war years in the estimates of the CIA - Mamedov Zaur Imalverdi oglu (Studia Humanitatis, 2024)
The article examines the process of the CIA’s analytical intelligence on the issue of the Soviet agriculture. American analysts investigated the intensification of this industry, its weaknesses and strengths, as well as the possibility of using the information received and the conclusions drawn in psychological warfare. Although agriculture in the USSR worried the CIA in the second place, but within the framework of the methodology adopted by American intelligence, the US “father of analytical intelligence” Sherman Kent contributed to a full-fledged study of the enemy in the Cold War.